2022
DOI: 10.3390/diagnostics12102501
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Puzzle: Oocyte Maturation Abnormalities (OMAS)

Abstract: Oocyte maturation abnormalities (OMAS) are a poorly understood area of reproductive medicine. Much remains to be understood about how OMAS occur. However, current knowledge has provided some insight into the mechanistic and genetic origins of this syndrome. In this study, current classifications of OMAS syndromes are discussed and areas of inadequacy are highlighted. We explain why empty follicle syndrome, dysmorphic oocytes, some types of premature ovarian insufficiency and resistant ovary syndrome can cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Repeated EFS may be associated with premature oocyte atresia or oocyte maturation disorders, with the oocytes obtained presented as germinal vesicle (GV) or MI stage ( 25 ), immature oocytes without zona pellucida ( 26 ), or with an identifiable zona but devoid of oocytes ( 27 ). Our study identified two patients with repeated EFS, whose oocytes were all in the MI stage with abnormal zona pellucida, consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated EFS may be associated with premature oocyte atresia or oocyte maturation disorders, with the oocytes obtained presented as germinal vesicle (GV) or MI stage ( 25 ), immature oocytes without zona pellucida ( 26 ), or with an identifiable zona but devoid of oocytes ( 27 ). Our study identified two patients with repeated EFS, whose oocytes were all in the MI stage with abnormal zona pellucida, consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although PATL2 expression is almost undetectable after extrusion of the first polar body in normal oocytes, early dysfunction has a subsequent effect on oocyte outcome. Recently, the results of the study by Hatirnaz and team provided the hope of pregnancy for patients with oocyte maturation abnormalities ( Hatirnaz et al, 2022 ). According to the Hatirnaz and Dahan Classification System, the ongoing pregnancy in women with type II (MI arrest) and type V (GV, MI and MII mixed arrest) oocyte seemed to be achieved by dual stimulation in in vitro maturation (Duastim IVM) in the Hartinaz clinic; this did not include patients with Type I (GV arrest), Type III (MII arrest) and Type IV (GV-MI arrest) oocyte abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…One patient had two failed IVF attempts because of GV arrest by PANX1 mutation and was treated with letrozole priming IVM, and one fertilised embryo was obtained, giving the PANX1 mutation oocyte a living potential. Therefore, this led to an important step forward in therapy ( Hatirnaz et al, 2022 ). But at present the patients with pathogenic mutations are still suggested to stop the recurrent self oocyte attempts and refer to a oocyte donation strategy.…”
Section: Discussionmentioning
confidence: 99%